USG Changes in Different Kidney Diseases of Children - Rahman, Md. Mostafizur; Khatoon, Soofia; Banu, Nazneen Akhter; Ferdous, Bilkis; Ahmed, Ashrafuddin; Mridha, Md. Al-Amin (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll, 2011; 3 (1): 8-12 DOI: http://dx.doi.org/10.3329/jssmc.v3i1.12053